Interrelation of tolerance of the person and features of psychological adaptation of the chinese students - Т S Medvedskaya (Peoples' Friendship University of Russia (RUDN University), 2010)
The article is devoted to the tolerance and psychological adaptation of Chinese students to Russian environment. According to the level of ethnical adaptation and their correlation with ethnical, personal and social tolerance the groups of students are composed.